The Urgency of Socio-Legal Studies on the Political Configuration of the Job Creation Act’s Formation - Kriswanto Kriswanto (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
The The formation of laws and regulations in Indonesia must be understood comprehensively as a legal process as well as a political process. The legal process must be based on Law no. 12 of 2011 while the political process is obliged to look at the aspect of community deliberation to minimize the potential for conflict in the community. This study aims to analyze the CK Law and to suggest the urgency of socio-legal research in the formation of laws and regulations in Indonesia. This research is a socio-legal legal research that tries to look at the law internally and externally with the help of non-legal science, namely social science. This study uses primary legal materials in the form of UUCK and secondary legal materials in the form of journals, books, and related websites. Primary legal materials were analyzed using theories and concepts in secondary legal materials. This research uses a conceptual approach and a statutory approach The results of the study confirm that Ralf Dahrendorf's Conflict Theory in the Establishment of the CK Law emphasizes that the drafting and ratification of the CK Act is not optimal in involving quasi-groups or groups with high and low bargaining positions. In addition, the urgency of socio-legal analysis in the formation of laws and regulations in Indonesia is needed because when based on a socio-legal analysis a law does not have sociological validity, the law has the potential to cause conflict in society and even has the potential to be canceled by the Court. Constitution through formal review.